Subcronic Toxicity Of Moringa Leaf Extract (Moringa Oleivera L) On Histopathology Heart Organ Of Rats - yunda putri listiani; Novi - Ayuwardani; susanti - erikania (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Moringa leaf (Moringa oleivera L) is a plant that has benefits as a natural medicinal ingredient. Benefits of Moringa leaves as anti-inflammatory, antimicrobial, antioxidant, antihypertensive, anticholesterol and antidiabetic. Phytochemical test Moringa leaves contain flavonoids, alkaloids, saponins, tannins, phenols and steroids. Sub-chronic toxicity test was conducted to determine the negative impact of Moringa leaves on the body if consumed for a certain period of time. The test animals used were 20 male rats with 5 doses of treatment. Parameters observed were body weight (g), relative weight of liver (%), macroscopic changes and liver histopathology. The data were analyzed by One Way Anova and continued with the Post Hoc LSD test. The results of this study showed changes in body weight of rats, changes in the relative weight of the liver, macroscopic changes in the liver in the form of consistency and surface of the liver and histopathological changes in the liver in the form of necrosis with a total liver damage of 46% and the number of normal cells by 54%. Keywords: Moringa Leaf, Subchronic Toxicity, Liver Histopathology.